(untitled) (International Journal of Environmental Sciences, 2025)
The complex interplay of economic growth and the endeavour for environmental sustainability, continues to be a major challenge in the 21st century. The present study investigates the objective of Gross Domestic Product (GDP) and carbon emissions in India, where fossil fuels accounts for about 73% of the energy mix, is a rapidly developing economy. The research, based on the premise that growth in GDP leads to a proportional rise in carbon emissions, relies entirely on secondary data from the Worldometer Databases over 2001–2016 with cross-validation against Macroeconomic Trends archives. The methodology employs a quantitative design integrating inferential statistics and correlation analysis. First, a Student’s t-test was applied at a 0.05 significance threshold to test the existence of a relationship between GDP and carbon emissions. Second, Pearson correlation analysis was conducted to quantify thestrength of association between the two variables. Ethical considerations were addressed through systematic source verification, including the CRAAP framework for currency, relevance, authority, accuracy, and purpose. The results demonstrate a highly significant statistical relationship (p < 0.001) between GDP and carbon emissions. The correlation coefficient (r = 0.9822) reveals a very strong positive linear association, affirming that increments in India’s GDP are accompanied by nearly proportionate increases in carbon emissions. These findings validate the hypothesis and corroborate earlier scholarship that links economic expansion with intensified environmental degradation, particularly through greenhouse gas accumulation. The discussion situates these findings within global sustainability debates, emphasizing that India’s trajectory exemplifies the environmental costs of growth reliant on non-renewable energy. While economic expansion has delivered enhanced productivity and industrialization, it has simultaneously entrenched pathways of carbon dependency that exacerbate global warming and ecological deterioration. The study acknowledges limitations, particularly the exclusion of confounding variables such as urbanization, technological innovation, and trade openness, which may also influence emissions dynamics. Policy implications are twofold: (i) stricter regulatory frameworks to curtail carbon-intensive energy consumption, including vehicular emissions and industrial fuel use, and (ii) accelerated integration of renewable energy technologies to decouple growth from environmental harm. This research underscores the urgent need for multivariable, interdisciplinary approaches to environmental economics that move beyond GDP as the sole explanatory factor and advance frameworks for sustainable growth in developing economies.